2009
DOI: 10.1111/j.1582-4934.2009.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

AMPK‐mediated autophagy inhibits apoptosis in cisplatin‐treated tumour cells

Abstract: The role of autophagy in cisplatin anticancer action was investigated using human U251 glioma, rat C6 glioma and mouse L929 fibrosarcoma cell lines. A dose- and time-dependent induction of autophagy was observed in tumour cells following cisplatin treatment, as demonstrated by up-regulation of autophagy-inducing protein beclin-1 and subsequent appearance of acridine orange-stained acidic autophagic vesicles. The presence of autophagosomes in cisplatin-treated cells was also confirmed by electron microscopy. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 58 publications
12
93
0
1
Order By: Relevance
“…However, they also found augmented cisplatin sensitivity by metformin in a mouse melanoma cell line. Harhaji-Trajkovic et al (19) reported the antagonistic action of metformin on cisplatin. These findings again suggest that metformin affects different types of cancer, differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they also found augmented cisplatin sensitivity by metformin in a mouse melanoma cell line. Harhaji-Trajkovic et al (19) reported the antagonistic action of metformin on cisplatin. These findings again suggest that metformin affects different types of cancer, differently.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, the precise mechanisms of the metformin-induced effects are not fully understood. In particular, controversy remains about whether metformin is apoptotic (6,10) or just cytostatic (5,9) and whether it kills cancer cells synergistically with cytotoxic agents including cisplatin (11,13), paclitaxel (8), and doxorubicin (17), or if it is antagonistic to cisplatin (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…cisplatin), and to naturally occurring molecules (e.g. polyphenols), which have been considered to be promising anticancer drugs owing to their ability to induce metabolic oxidative stress (Harhaji-Trajkovic et al, 2009;Filomeni et al, 2010b). In light of these results, it is reasonable to consider that although targeting AMPK remains a feasible approach to selectively kill tumor cells, the possible activation of AMPKmediated pathways mediating tumor resistance, such as autophagy, should be taken into account.…”
Section: Ampk As a Target In Anti-cancer Therapiesmentioning
confidence: 99%
“…32,33 Recently, it has been reported that induction of autophagy is frequently observed in many human cancer cell lines treated with chemotherapeutics. [34][35][36] However, whether autophagy induced by chemotherapy acts as a protective mechanism that allows treated cancer cells to survive or rather as an alternative cell death-inducing process has been an issue of great controversy. Although MTOR plays an inhibitory role in regulation of autophagy, little is known about the role of autophagy in the chemotherapy of cancers driven by aberrant activation of MTOR signaling.…”
Section: Introductionmentioning
confidence: 99%